The Effect of Financial Literacy Level and Demographic Factors on Investment Interest in Satya Wacana Christian University Students - Febrynanda, Trivena; Martono, Samuel (Jurnal Manajemen, 2023)
The development of the financial sector growing very fast nowadays. This condition must be balanced by knowledge and ability in managing finances, including investments. Interest in investing is influenced by a lot of factors, and some of them are financial literacy and demographic factors (age, gender, faculty, GPA, and income). This research aims to identify the effect of financial literacy level and demographic factors on investment interest among Satya Wacana Christian University students in Salatiga. This research used quantitative methods that measured and analyzed related variables that have a cause-and-effect relationship with investment interest. The research data was obtained by distributing questionnaires to 362 students and analyzing them using multiple linear regression methods and SPSS 23 software. The results of this research show that financial literacy and demographic factors have a positive effect on student investment interest. Financial literacy showed a positive correlation, which proved that the higher the understanding of financial literacy, the higher the interest in investing. Demographic factors (age, gender, faculty, GPA, and income) also show influence on investment interest. From the results of this study, it is hoped that students will be more aware of the importance of knowledge about financial literacy so that they can increase their interest in investing.